GIS-based NR property rental information system case study: NR management unit, Universiti Teknologi MARA, Shah Alam / Rohana Ishak - Ishak, Rohana (Faculty of Architecture , Planning and Surveying, 2010)
This Thesis discuss about a research with the aim of utilizing the Geographic Information System (GIS) in Real Estate sector namely specifically in Field of Estate Agency by design and develop spatial database ( a GIS system) called as GIS-Based NR Property Information System to Non Resident Management Unit or more known as NR Management Unit. The development of the spatial database is using GIS software namely ArcGIS 9.3 and some of GIS operation.This research commencing with planning stage namely study of user requirement, then followed by implementation stage namely involve process of preparation of software and hardware, data collection and creation of spatial data base. Next, analysis stage namely using GIS function such as “Select by Attribute”,“Select by Location”, and “Intersect”. Finally evaluation stage involves recommendation and conclusion. This research uses an informal method i.e. structure interview and review of existing information system in order to identify problem, selection of thesis title, and lastly decide research objective, significant and scope. There are 2 type of data used in develop this system namely spatial (geometric) and attribute data. Spatial data used is several Maps of Shah Alam areas namely Map of Community Facilities, GPS Map and Street Directory Map.Attribute data used is listing of rental houses that contain information such as type of house, rental price, rental type, contact number, contact person, number of bedroom, number of bathroom and others.